The Influence of Emotional Intelligence, School Environment, Teacher Role, and Peers on Student Learning Discipline Through Learning Motivation as an Intervening Variable for Grade VIII Students in Integrated Social Studies Subjects at SMP N 2 Bonjol - Ratna; Stevani; Fifi Yasmi (Journal of Classroom Action Research, 2025)
This study aims to analyze the influence of emotional intelligence, school environment, teacher role, and peer group on the motivation and learning discipline of students at SMP N 2 Bonjol. Using a quantitative approach with an associative research method, data were obtained from 100 students selected through proportional random sampling. Analysis was conducted using path analysis. The results showed that emotional intelligence, teacher role, and peer group had a positive and significant influence on learning motivation, while the school environment did not have a significant influence. Furthermore, all independent variables, including learning motivation, were proven to have a positive and significant influence on student learning discipline. Based on these findings, it is recommended that students continue to develop emotional intelligence and positive relationships with peers. Teachers are expected to be motivators and role models of discipline, schools need to create a conducive learning environment, and parents should provide emotional support and supervision so that disciplined learning habits can be formed comprehensively.